Opportunities for Using Complexity-Aware Approaches to Theory of Change - Goodier, Sarah; Apgar, Marina (IDS, 2018)
The purpose of this briefing note is to review opportunities for using complexity aware approaches to Theory of Change (ToC) to inform the SDC approach. It provides an overview of complexity-aware approaches and then focuses on demonstrating how complexity thinking can support programming by building on the frameworks currently being used in the project/programme cycle management (PCM) processes. It is aimed at SDC staff, in particular Programme Officers and staff of partner organisations involved in the management of SDC interventions.

State of the Art on Use of Theory of Change in the Development Sector - Goodier, Sarah; Apgar, Marina; Clark, Louise (IDS, 2018)
The purpose of this briefing note is to add to SDC’s understanding of Theory of Change (ToC), drawing on the literature and practice to sketch out the current state of the art approach. This involves expanding on ToC beyond SDC’s current practice of using Impact Hypotheses (IH) to bridge it to operational practice and use ToC more explicitly in the project/programme cycle management (PCM) processes. Sharing the state of the art on use of ToC in the development sector, this briefing note outlines what a ToC is, what it is used for and why it is needed in the development sector. It discusses ToC as both a process and a product, providing step by step guidance on how to facilitate a ToC process. The differences between a ToC and a logframe are highlighted. Some key criteria for recognising when you have a ‘good’ ToC are also included. This brief is aimed at SDC staff, in particular Programme Officers, and staff of partner organisations involved in the management of SDC interventions.

Adaptive Management in SDC: Challenges and Opportunities - Prieto Martin, Pedro; Apgar, Marina; Hernandez, Kevin (IDS, 2020)
Adaptive management (AM) is a programme management approach that helps international development organisations to become more learning-oriented and more effective in addressing complex development challenges. AM practices have been applied for decades within other sectors as varied as logistics, manufacturing, product design, military strategy, software development and lean enterprise. At its core, AM is not much more than common sense, as it essentially recognises that the solutions to complex and dynamic problems cannot be identified at the outset of a programme but need to emerge throughout the process of implementation as a result of systematic and intentional monitoring and learning. The generic AM process typically involves an iterative cycle of design, implementation, reflection and adaptation activities, supported both by system monitoring and stakeholder involvement to obtain a better understanding of the evolving system and improve how the intervention is managed. A favourable context for AM in development. During recent decades, the international development sector has aimed to increase its results and impact orientation. As a result, a growing number of development organisations and governments have become increasingly aware of the limitations of traditional ‘linear and prescriptive’ programming approaches. They are now recognising the need to handle complexity better, and have begun to adapt their policies and practices to facilitate adaptive approaches. The World Bank, for example, now acknowledges that aid agencies need to increase flexibility of implementation, tolerate greater risk and ambiguity, devolve power from aid providers to aid partners, and avoid simplistic linear schemes for measuring results. Multilateral and bilateral organisations such as the World Bank, the United Kingdom’s (UK) Department for International Development (DFID) and the United States Agency for International Development (USAID) are currently experimenting with adaptive approaches. A multitude of adaptive approaches and communities of practice have emerged that aim to improve the effectiveness of aid, including Collaborating, Learning, and Adapting, Thinking and Working Politically, Doing Development Differently, Market Systems Development, Conflict-Sensitive Programme Management, and Science of Delivery. Since generic AM approaches have existed for decades in other sectors, AM has the potential to act as a neutral ‘bridge language’ that facilitates exchange and learning among the different communities and donors. This report is the result of a learning partnership between the Swiss Agency for Development and Cooperation (SDC) and the Institute of Development Studies (IDS). It assesses the relevance of AM to SDC, how it relates to working practices across SDC, and the key challenges and opportunities for SDC. Its process of elaboration involved a literature review on AM, an exploration of AM approaches from several bilateral donors, a series of 6 interviews with SDC staff and partners working in different countries and thematic domains, and a learning workshop at SDC headquarters (HQ), where staff from several SDC divisions reflected on AM and on how to advance the organisation’s capacity for adaptive programming and learning.